Transcranial direct current stimulation as a treatment for auditory hallucinations - Koops, Sanne; van den Brink, Hilde; Sommer, Iris E. C. (Frontiers in Psychology, 2015)
Auditory hallucinations (AH) are a symptom of several psychiatric disorders, such as schizophrenia. In a significant minority of patients, AH are resistant to antipsychotic medication. Alternative treatment options for this medication-resistant group are scarce and most of them focus on coping with the hallucinations. Finding an alternative treatment that can diminish AH is of great importance. Transcranial direct current stimulation (tDCS) is a safe and non-invasive technique that is able to directly influence cortical excitability through the application of very low electric currents. A 1-2 mA direct current is applied between two surface electrodes, one serving as the anode and the other as the cathode. Cortical excitability is increased in the vicinity of the anode and reduced near the cathode. The technique, which has only a few transient side effects and is cheap and portable, is increasingly explored as a treatment for neurological and psychiatric symptoms. It has shown efficacy on symptoms of depression, bipolar disorder, schizophrenia, Alzheimer’s disease, Parkinson’s disease, epilepsy and stroke. However, the application of tDCS as a treatment for AH is relatively new. This article provides an overview of the current knowledge in this field and provides guidelines for future research.